AHP-SMART Method as Evaluation Decision Support for Employee Promotion - Akmaludin, Akmaludin; Suriyanto , Adhi Dharma; Iriadi, Nandang; Sukendar, Toni; Santoso, Budi (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Evaluation of the quality of employees in an institution is very necessary, especially for promotions which are the rights of every employee in leading a company that is full of competition. The purpose of this paper is to contribute in terms of the evaluation process in selecting employees who are ready to be promoted in a particular institution. With the support of various parties, a consistent and optimal method is needed to carry out the evaluation process, which is a popular priority, it is recommended to use the AHP-SMART method, where this method will be collaborated to become a core unit of problem solving, especially in terms of promotion as evaluation and selection material. Selection of the best employees, The AHP method will be used to conduct an assessment of the criteria used with the concept of Multi-criteria Decision Making (MCDM) which utilizes the results obtained from the eigenvector through iteration to minimize differences in the assessments of a number of respondents, while the SMART method is used to determine the results of decisions in collaboration with the AHP method, especially in terms of benefit utility and cost utility. The criteria used as an assessment measure consist of Planning, Solution Capture, Knowledge of Job, Reaction Behavior, Quantity of Works, Failed of Jobs, and Depandibility. The final result of the collaboration process of the two methods AHP and SMART gives a ranking of 26 employees with the highest score and being selected through an evaluation process for promotion won by K23 with a ranking weight (73.19) and the second is followed by K2 (76.17) and ranked the third was won by K3 (56.95). Thus the selection and evaluation process for promotion can be recommended and used as an optimal process from the selection stages of employee selection for promotion in every company agency.